SECURITY AND SCALABILITY: CORNERSTONES OF INDUSTRIAL IOT NETWORK ARCHITECTURE - Amith Ronad, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The Industrial Internet of Things (IIoT) has emerged as a transformative force in manufacturing, utilities, and industrial processes, fundamentally changing how organizations approach operational efficiency and productivity. As industrial facilities increasingly rely on interconnected devices and sensors, security and scalability have become critical success factors in IIoT deployments. This article examines the integration of security and scalability in IIoT networks, exploring multi-layered security architectures, scalability frameworks, and implementation strategies. Through analysis of current industry practices and emerging technologies, it provides a comprehensive framework for organizations seeking to establish or enhance their IIoT infrastructure, addressing both immediate operational needs and long-term strategic objectives in the rapidly evolving industrial digital landscape.